Evaluation of bioelectrical activity of masseter muscles in women with myogenic disorders of the stomatognathic system - Gębska, Magdalena; Opalko, Krystyna; Rynio, Piotr; Weber-Nowakowska, Katarzyna; Żyżniewska-Banaszak, Ewelina; Garczyński, Wojciech; Kołodziej, Łukasz (Akademia Wychowania Fizycznego w Poznaniu)
Background. One of the etiological factors of the stomatognathic system (SS) disorders is excessive tension and muscle activity. These factors are associated with long-term non-physiological overload of SS tissues. Palpation of masticatory muscles allows for subjective assessment of muscle tension and tenderness. One of the available tools which are an important part of the examination is non-invasive global electromyography − sEMG (ang. surface electromyography). Objective. The aim of the study is to evaluate the bioelectrical activity of masseter muscles inpatients with stomatognathic disorders. All disorders are myogenic origin. In addition reference standards for the masseter muscle in healthy people will be definied. Material and Methods. The study was conducted in a group of 104 women (Group I) with a myogenic pain disorders. All women were examined sEMG masseter muscles at rest and during maximal contraction. To defined standarized vaues for the masseter muscle authors formed a control group (Group II). Results. Comparison of the two groups revealed statistically significant differences in amplitude sEMG masseter muscle. In Group I, the average value of the amplitude of the EMG masseter muscle at rest and during maximal contraction is higher than in Group II. Conclusions. The results testify to generating greater static and dynamic loads on the surfaces of the temporomandibular joints. The higher amplitude values in female group with myogenic disorders of the SS confirms that in patients with myogenic pain disorders sEMG test is a valuable addition to the diagnosis.
Keywords: surface electromyography; stomatognathic system; masseter muscle